2022
DOI: 10.1177/20499361221108005
|View full text |Cite
|
Sign up to set email alerts
|

Design and protocol of the Buprenorphine plus Outpatient Parenteral Antimicrobial Therapy (B-OPAT) study: a randomized clinical trial of integrated outpatient treatment of opioid use disorder and severe, injection-related infections

Abstract: Introduction: A marked increase in hospitalizations for severe, injection-related infections (SIRI) has been associated with the opioid epidemic. Outpatient parenteral antibiotic therapy (OPAT) is typically not offered to persons with opioid use disorder (OUD) and SIRI, though increasing evidence suggests it may be feasible and safe. This study evaluates the efficacy and cost-effectiveness of an integrated care model combining Buprenorphine treatment of OUD with OPAT for SIRI (B-OPAT) compared with treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…These results illustrate clinicians’ understanding that management of infectious complications of IDU requires not only optimizing antimicrobial management but also treatment of underlying SUD and linkage to care after discharge. Several studies have shown that pairing courses of OPAT with addiction treatment can lead to favorable outcomes, and there is an ongoing prospective randomized clinical trial assessing the efficacy of pairing OPAT with buprenorphine [ 11 , 12 , 20 ]. A structured multidisciplinary approach to discharge decision-making that includes case management and linkage to outpatient addiction care has been shown to be effective in creating individualized care plans [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results illustrate clinicians’ understanding that management of infectious complications of IDU requires not only optimizing antimicrobial management but also treatment of underlying SUD and linkage to care after discharge. Several studies have shown that pairing courses of OPAT with addiction treatment can lead to favorable outcomes, and there is an ongoing prospective randomized clinical trial assessing the efficacy of pairing OPAT with buprenorphine [ 11 , 12 , 20 ]. A structured multidisciplinary approach to discharge decision-making that includes case management and linkage to outpatient addiction care has been shown to be effective in creating individualized care plans [ 21 ].…”
Section: Discussionmentioning
confidence: 99%